2016
DOI: 10.14238/pi46.3.2006.127-33
|View full text |Cite
|
Sign up to set email alerts
|

The role of bovine colostrum on recovery time and length of hospital stay of acute diarrhea in infants and children: a double-blind randomized controlled trial

Abstract: A cute diarrhea is remains a major problem of morbidity and mortality in the most de veloping countries. According to the Sensus Kesehatan Rumah Tangga (SKRT) in year of 2002, the cumulative incidence of acute diarrhea in Indonesia was 127.8% or 1.3 episode/children below 5 year old per year. In Bali, the incidence of acute diarrhea in the children below 5 year old was 62.1%. 1,2The most frequent etiology of acute diarrhea is viral, bacterial, parasite, and fungal infections. Virus is the most frequent etiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
(15 reference statements)
2
1
0
7
Order By: Relevance
“…Ylitalo et al showed that [29] infants and children suffered from rotavirus-caused acute diarrhea had a significant increase in body weight (403 g) after given bovine colostrum for 4 days as compared to the control group (343 g). However, the study performed by Suwarba [18] showed no effect of BC intervention on the children's body weight, which was in agreement with our study.…”
Section: Effect On the Anthropometric Indicessupporting
confidence: 92%
See 1 more Smart Citation
“…Ylitalo et al showed that [29] infants and children suffered from rotavirus-caused acute diarrhea had a significant increase in body weight (403 g) after given bovine colostrum for 4 days as compared to the control group (343 g). However, the study performed by Suwarba [18] showed no effect of BC intervention on the children's body weight, which was in agreement with our study.…”
Section: Effect On the Anthropometric Indicessupporting
confidence: 92%
“…Some studies have reported adverse reactions to BC such as nausea, vomiting, headache, insomnia, pruritus, and myalgia, which might be caused by the allergy to the protein components in BC [13][14][15] . The present investigation and many other studies [16][17][18] did not find any adverse reaction or intolerance to BC. Thus, BC is safe to be given to infants and children without allergy or intolerance to cow's milk.…”
Section: Discussionsupporting
confidence: 67%
“…The treatment reduced the intensity of diarrhea (number of stools) and shortened its duration and the period of virus excretion from the body [ 31 , 32 , 33 ]. Meanwhile, in children infected with Escherichia coli or Shigella , a reduction in the frequency of bowel movements and vomiting, faster elimination of pathogens from the body and a shorter period of necessary hospitalization were observed after the application of these preparations [ 34 , 35 ]. A 2019 meta-analysis that included five RCTs in children with diarrhea and confirmed rotavirus or E. coli infection (total n = 324) demonstrated the efficacy of BC, HBC and Igs isolated from HBC.…”
Section: Bovine Colostrummentioning
confidence: 99%
“…7 Selain itu, pemberian kolostrum dapat mempercepat kesembuhan pasien diare akut pada bayi dan anak balita, pemberian suplemen zink juga dapat mempercepat kesembuhan pasien diare akut pada anak. 8,9 Lama rawat pasien diare akut di BRSU Tabanan secara keseluruhan hampir sama dengan beberapa rumah sakit lain, akan tetapi lama rawat untuk pasien dengan dehidrasi berat ternyata lebih lama. 10 Hasil penelitian Yusuf tahun 2010 diperoleh data tentang profil diare di ruang rawat inap anak RSUD Zainoel Abidin, Banda Aceh, yaitu sebagian besar lama perawatan (90,4%) kurang dari lima hari.…”
Section: Bahasanunclassified